Analysis of the Effectiveness of Adaptive Governance in Managing Natural Resource Conflicts (The Case of Mining in the Sorowako Region) - Dahlia Wirawan (Adaptive Governance Research, 2024)
Purpose: This examine investigates the dynamics of adaptive governance in dealing with herbal useful resource conflicts, focusing at the Sorowako vicinity's mining sports activities. Subjects and Methods: Through a mixed-techniques method, which includes descriptive information, paired-samples t-checks, regression analyses, ANCOVA, and Pearson correlational analyses, the research explores stakeholder pleasure and governance effectiveness. Results: Findings display screen the pivotal roles of community participation, institutional collaboration, and stakeholder engagement in enhancing adaptive governance mechanisms. Significant close by variations in stakeholder delight underscore the need for context-precise processes. Conclusions: The test contributes insights to useful aid management and emphasizes the significance of inclusive decision-making strategies.